A Preliminary Study on the Biased Attention and Interpretation in the Recognition of Face-Body Compound of the Individuals with Social Anxiety - Kim, Dong-Hyun; Lee, Jang-Han (Frontiers in Psychology, 2016)
The present study aimed to investigate the processes through which individuals with social anxiety attend to and interpret compound emotional expressions of the face and body. Incongruent face-body compound images that combined an angry face (or body) with a fearful, sad, or happy body (or face) were presented to a social anxiety group (SA; n=22) and a healthy control group (HC; n=22). The participants were instructed to interpret the emotional state of the image, and their eye-movements and behavioral responses were measured. The results revealed that both group showed longer scanpath length during the recognition of compound images which combined angry face with angry, fearful, sadness, or happy body. The SA group also showed longer scanpath length in congruent face-body compound images of fear and sad. Additionally, the SA group fixated for a shorter period of time on the face and longer on the body than the HC group. Regarding emotion interpretation, the SA group was more likely to interpret the emotional state of incongruent face-body compound images based on the body than the HC group. These findings provide a preliminary observation that individuals with social anxiety showed different attentional bias pattern by congruency of face-body compound images and that it might have biased their interpretations of the emotional states.